2011
DOI: 10.4067/s0718-381x2011000200001
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoma in the Oral Cavity: A Case Report

Abstract: The plasma cell neoplasms may present in soft tissue as extramedullary plasmacytoma (EMP), in bone as a solitary plasmacytoma of bone (SPB), or as part of the multifocal disseminated disease multiple myeloma (MM). The EMP is rare, comprising around 3% of all plasma cell neoplasm. The majority (80%) occurs in the head and neck region. In this study we report a case of a man, 70 years old, melanoderm, with a lesion of the oral cavity. Upon physical examination, a lesion was found that extended throughout the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…When diagnosed early and when there is no bone involvement, treatment success is usually greater. The treatment of choice is radiotherapy, which leads to good results in relation to the remission of the lesion [6]. The option for surgical resection can be considered in case of small lesions or for correction of functional or aesthetic defects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When diagnosed early and when there is no bone involvement, treatment success is usually greater. The treatment of choice is radiotherapy, which leads to good results in relation to the remission of the lesion [6]. The option for surgical resection can be considered in case of small lesions or for correction of functional or aesthetic defects.…”
Section: Discussionmentioning
confidence: 99%
“…Edema is the most common complaint and painful symptomatology can be reported when there is involvement of the underlying bone. Discomfort or pain in the dental element may occur when the lesion involves the region of the dental alveolus [6].…”
mentioning
confidence: 99%
“…It can be divided in two groups depending on its location: solitary bone plasmacytoma (SBP) and solitary extramedullary plasmacytoma (EMP). Multiple myeloma (MM) is the systemic form of the pathology, characterized by multifocal disseminated lesions, and represents the most common tumor of plasma cells [ 1 , 2 ]. Both subtypes of solitary plasmacytoma can progress to multiple myeloma, but this occurrence is more common in SPB [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…EMP can involve any site or organ, but it is estimated that nearly 80% of cases arise in the subepithelial tissues of the head and neck region, and especially the upper respiratory tract (nose, paranasal sinuses, nasopharynx, and tonsils) for which patients usually experience swelling and moderate pain in the affected area [ 5 , 8 ]. A review of the medical literature revealed that only a small number of patients are reported with EMP of the oral cavity, especially with the involvement of the palate [ 2 , 3 , 6 , 8 , 9 , 10 , 11 ]. Some authors have reported the case of a patient presenting with a painless, rapidly growing lesion in the posterior upper alveolar ridge that extended towards the palate, [ 2 ] while others described a case of EMP presenting as a massive exophytic lesion of the hard palate that was covered with intact mucosa [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although rare, there is some evidence that may be found an extramedullary plasmacytoma when this pathological condition involvement exclusively affects the soft tissue [ 3 ]. It is noteworthy that when localized monoclonal proliferations of plasma cells occur, its progression to multifocal disseminated disease and multiple myeloma appears to be a common event―approximately 80% of cases―and, under these circumstances, the disease represents the most important, most severe and common plasma cell dyscrasia [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%